The reliability of dental panoramic tomographs in determining the upper and lower third molar root morphology - Gačić Bojan; Ilić Branislav; Bakalović Jovana; Mitrović Marija; Kuzmanović-Pficer Jovana; Jovičić Bojan; Janjić Bojan (Vojnosanitetski Pregled)
Background/Aim. The shortcomings of the orthopantomography (OPG) method and radiographic misinterpretations may lead to poor treatment planning and complications during or after the third molar extraction. The aim of this study was to determine the validity and reliability of OPG findings concerning post-extraction wisdom tooth root morphology, as well as whether the degree of clinical expertise affects assessment accuracy. Methods. The cross-sectional study included 200 patients who were referred for third molar extraction. Preoperative OPGs were evaluated by the examiners, who were classified by their level of experience into three groups: students, residents, and professors. True root morphologies were recorded after the extraction, and the accuracy of the assessment was evaluated using various statistical tests. Results. The majority of assessments were accurate for the lower and upper third molars with a single root. The professor group was the most accurate when compared to the assessments made by the students and residents (p = 0.0015). Weighted Cohen’s kappa (κw) values for intra-respondent accuracy gradually increased from the student to professor group (0.06, 0.28, 0.34, respectively). The highest discrepancy in inter-respondent accuracy was determined between the student and professor groups (poor; κw = 0.25584). Conclusion. In this study, the results that confirm the reliability of the OPG scan for the detection of accurate third molars root morphology have not been achieved. The level of clinical experience affects diagnostic accuracy, but complex clinical cases should be evaluated using different methods.